FENOMENA FASHION SYAR’I SEBAGAI TREND BUDAYA MENURUT AKIDAH ISLAM (STUDI ANALISA DI UNIMED PADA FAKULTAS SENI DAN BUDAYA) - Mardhiah Abbas; Nurliana Damanik; Nurmi Nurmi (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
This research was conducted at Medan State University where the aim was to find out the phenomenon of Syar’I fashion as a cultural trend according to Islamic aqeedah. This study examines broadly how the Syar’I fashion is among students, how their responses and responses are related to Syar’I fashion which has increasingly advanced in this day and age. Because along with the times that make it able to develop. As well as how the worl view of the West, East, The Qur’an, Hadith and culture see the fashion of the lighthouse. This reseacrch was surveyed based on field results, interviews and documentation. Keywords: Fashion, Culture, West, East, Al-Qur'an, hadith, Aqidah, Students.